The rediscovery of Heteragrion azulum Dunkle, 1989 with additional notes on the female (Odonata: Heteragrionidae) - Novelo-Gutiérrez, Rodolfo; Gómez-Anaya, José Antonio (Zootaxa, 2023)
Some details of the morphology of the female of Heteragrion azulum Dunkle, 1989 are described for the first time such as the intersternite, and illustrated with high quality photographs, based upon two specimens collected in the tropical rain forest at the region of Los Tuxtlas, in the state of Veracruz, Mexico. A comparison with females of the other three species of Heteragrion Selys, 1862 occurring in Mexico is also provided. Additional data of males of H. azulum collected together with the females are also given, including some illustrations.